2018
DOI: 10.1002/mas.21558
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion laser desorption/ionization time‐of‐flight mass spectrometric analysis of small molecules by using nanostructured substrate as matrices

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is an excellent analytical technique for rapid and sensitive analysis of macromolecules such as polymers and proteins. However, the main drawback of MALDI-TOF MS is its difficulty to detect small molecules with mass below 700 Da because of the intensive interference from MALDI matrix in the low mass region. In recent years there has been considerable interest in developing matrix-free laser desorption/ionization by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 110 publications
(185 reference statements)
0
28
0
Order By: Relevance
“…Matrix-Assisted Laser Desorption/Ionization–Time-of-Flight Mass Spectrometry (MALDI-TOF MS) is an important rapid identification tool in microbiology and is traditionally used for the identification and analysis of large biomolecules including proteins, peptides and nucleic acids (Lin and Cai, 2018). MALDI-TOF MS is based on the ionization of the biomolecules (such as proteins) of an organism of interest, co-crystallized with a chemical acidic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-Assisted Laser Desorption/Ionization–Time-of-Flight Mass Spectrometry (MALDI-TOF MS) is an important rapid identification tool in microbiology and is traditionally used for the identification and analysis of large biomolecules including proteins, peptides and nucleic acids (Lin and Cai, 2018). MALDI-TOF MS is based on the ionization of the biomolecules (such as proteins) of an organism of interest, co-crystallized with a chemical acidic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles have strong UV absorption capacity and hot carrier property under laser excitation, enhancing the analytes′ desorption and ionization [24] . However, the single noble metal nanoparticles with simple morphology are easy to agglomerate in small molecule analysis, forming abundant background interfering ions with decreased sensitivity and selectivity (metal‐cluster species) [25] . To address these drawbacks, noble‐metal has been modified on various matrices in advanced small molecule detection.…”
Section: Nanocomposites and Their Applicationmentioning
confidence: 99%
“…A number of reviews are devoted to the use of nanoparticles in SALDI. [3][4][5][6] Another variant of the SALDI method is based on using monolithic substrates with a specially prepared surface layer. A major advance in this direction came in 1999, when Wei et al reported that high-quality mass spectra could be obtained from organic compounds deposited as a solution on a porous silicon substrate.…”
Section: Introductionmentioning
confidence: 99%